PENGEMBANGAN LEMBAR KEGIATAN PESERTA DIDIK (LKPD) BERBASIS PROBLEM BASED LEARNING DI SERTAI SOAL HIGH ORDER THINKING SKILL (HOTS) TERHADAP KEMAMPUAN BERPIKIR KRITIS PADA PEMBELAJARAN BIOLOGI MATERI SISTEM REPRODUKSI - Jasmia Okista Meliza; Handoko Santoso; Agil Lepiyanto (Prodi Pendidikan Biologi FKIP Universitas Muhammadiyah Metro, 2021)
This development research aims to produce a product in the form of Development of Student Activity Sheets based on Problem Based Learning Accompanied by High Order Thinking Skills (HOTS) on critical thinking skills in learning biology of reproductive system material that is appropriate for students to use. This research development uses qualitative research methods with the Research & Development model suggested by Borg & Gall by using 6 stages out of 10 stages, namely Collecting of research and information, Planning, Developing a preliminary form of product, Preliminary field testing, Operational field testing, Operational product revision, Main field testing, Main product revision, Final product revision, and Dissemination and implementation. The results of the development carried out from the validation of design experts obtained a percentage of 90%, from the validation of material experts obtained a percentage of 81.81%, and validation by biology subject teachers is 80%. The average value obtained from the results of expert validation is 83.93% with the description